(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to identify the anxiety of the future among sixth-grade middle school students in Al-Duha secondary school for girls, by preparing a pilot program to reduce the future anxiety of the research sample, and to test the research hypotheses, the experimental design with the same experimental group with the test (pre and post) was chosen, and for the purpose of Measuring future anxiety by means of a questionnaire form as it consisted of (48) paragraphs, and then preparing an indicative program where the number of sessions reached (14) indicative sessions for the duration of each session (45) minutes, and by the session of each week, and after data collection was treated using the statistical program spss , And the results of the study showed the existence of differences with d For a statistical machine on the scale of future anxiety of the sample, the research before and after the indicative program, at a level (0.05) indicating the effect of the proposed indicative program under discussion, and in light of the findings of the research, the researcher made a number of recommendations and proposals.